Treatment of neonatal abstinence syndrome in preterm and term infants - Dabek, Martin Thomas; Pöschl, Johannes; Englert, Stefan; Ruef, Peter (Klinische Pädiatrie, 2013)
Neonatal abstinence syndrome (NAS) is treated with a variety of drug preparations. With the optional treatment of NAS with chloral hydrate, phenobarbital or morphine the cumulative drug consumption of the mentioned drugs, the length of hospital stay and treatment duration was evaluated in preterm and term neonates. - - Retrospective, uncontrolled study which evaluates different therapies of neonatal abstinence syndrome (NAS) in preterm and term neonates. - - During the past 16 years data were obtained from medical records of 51 neonates with NAS; 9 preterm and 35 term neonates were evaluated and 7 were excluded because of incomplete data sets. 31 (72.1%) received a pharmacological treatment (6 preterm and 25 term neonates). Treatment started at 4.3 [3.3-5.3] d. Mean duration of treatment was 11.7 [6.6-16.7] d. In our study chloral hydrate (ch) and phenobarbital (pb) were first line medication escalated by the morphine (mp) solution. Mean cumulative dosage of ch was 643.5 [260.3-1 026.7] mg, of pb 53.2 [19.7-86.8] mg and of mp 4.22 [0-8.99] mg. - - Our study group showed similar treatment duration and length of hospital stay compared to other studies. The cumulative dose of mp was lower compared to most studies. This benefit resulted at the expense of a further medication with pb and ch. However, 6 of 9 preterm neonates needed significantly less pharmacological therapy compared to term neonates indicating less susceptibility of immature brain to abstinence of maternalopioids.
Gesehen am 01.06.2021